2000
DOI: 10.1063/1.481463
|View full text |Cite
|
Sign up to set email alerts
|

The formation of subsurface oxygen on Pt{110} (1×2) from molecular-beam-generated O2 Δg1

Abstract: Adsorption dynamics of CO 2 on Zn-ZnO(0001): A molecular beam study J. Chem. Phys. 122, 044705 (2005); 10.1063/1.1834490 CO-induced restructuring of Pt(110)-(1×2): Bridging the pressure gap with high-pressure scanning tunneling microscopy An unusually high-peak-temperature desorption state of O 2 from Pt͕110͖ (1ϫ2) has been characterized in temperature programmed desorption spectra after O 2 adsorption from a supersonic beam at a translational energy of 190 meV and at nozzle temperatures, T n , greater than 87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…SDO has been observed to react in some metal complex systems forming metastable oxygenated compounds, which are not formed with ground-state oxygen . Walker and co-workers also suggested that SDO is responsible for the formation of subsurface oxygen on Pt{100}(1×2) during molecular beam exposures . This excited state of oxygen is known to be populated in plasma discharges, sometimes to a high degree, and it is likely present in our plasma jet also, as suggested by Pollard .…”
Section: Resultsmentioning
confidence: 75%
“…SDO has been observed to react in some metal complex systems forming metastable oxygenated compounds, which are not formed with ground-state oxygen . Walker and co-workers also suggested that SDO is responsible for the formation of subsurface oxygen on Pt{100}(1×2) during molecular beam exposures . This excited state of oxygen is known to be populated in plasma discharges, sometimes to a high degree, and it is likely present in our plasma jet also, as suggested by Pollard .…”
Section: Resultsmentioning
confidence: 75%
“…The complete reduction of PtO 2 is observed above 750 K, while a small signal of Pt 2+ (∼13%) remains. The stronger stability of the PtO species on Pt/SiO 2 as compared to Pt/TiO 2 (Figure c) might indicate the existence of not just surface but also subsurface and/or interfacial Pt oxides. , The presence of subsurface oxygen on platinum was previously described by several other groups. The possible enhanced stability of PtO x species at the Pt/SiO 2 interface still needs to be explored. However, such effect is unlikely to be dominant for the latter system due to the small contact area of our 3D NPs with the SiO 2 support, its low reducibility, and the fact that no drastic changes were observed in the decomposition pattern of the Pt/SiO 2 sample upon annealing in UHV [Figure a (closed symbols)] versus O 2 [Figure a (open symbols)].…”
Section: Discussionmentioning
confidence: 82%
“…93,133 The presence of subsurface oxygen on platinum was previously described by several other groups. [133][134][135][136][137] The possible enhanced stability of PtO x species at the Pt/SiO 2 interface still needs to be explored. However, such effect is unlikely to be dominant for the latter system due to the small contact area of our 3D NPs with the SiO 2 support, its low reducibility, and the fact that no drastic changes were observed in the decomposition pattern of the Pt/SiO 2 sample upon annealing in UHV [Figure 11a (111) and ZrO 2 (011) has been reported by Alfredsson et al, 139 and contrary to the previous study, no evidence for charge transfer at the Pt/ZrO 2 interface was found.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of the pronounced CO peak around 2073 cm -1 clearly results from the oxidative pretreatment, which likely produced a PtO x surface oxide, [75][76][77][78][79][80] on which CO does not adsorb at 293 K (the weak 2115 cm -1 species may originate from CO-Pt nþ at the metal-support interface). Alternatively, a dense (compressed) layer of chemisorbed oxygen may prevent CO adsorption at 293 K. [81][82][83] In any case, CO exposure around room temperature did not reverse the effect of preoxidation; that is, CO reacted with neither PtO x 79 nor a dense oxygen adlayer (although it could account for the small metallic shoulder).…”
Section: Resultsmentioning
confidence: 99%